Analisis Karakteristik Anak Berkebutuhan Khusus Jenis Autisme Pada Sekolah Inklusif - Nisak, Nikita Hoirun; Harsiwi, Nova Estu (ALENA : Journal of Elementary Education, 2024)
This study aims to determine the characteristics of students with special needs of autism in inclusion schools. The research method used is qualitative descriptive with data collection techniques used in interviews, observations and documentation. Based on the results of the study, that students with special needs of autism have characteristics, namely children who look normal but have difficulties in communication, social interaction, behavior or attitude, unstable emotions, very high level of sensitivity, difficulties in writing, reading and understanding subject matter, activities that are carried out continuously and even permanently, desires and pleasures that are labil, Engrossed in playing alone and fascinated by an object that rotates or moves. Children with autism have characteristics in the areas of communication, social interaction, sensory, play patterns, behavior and emotions.